Métodos alternativos de enseñanza en bilingüismo, artes visuales y música como resultados de investigación en la Facultad de Bellas Artes y Humanidades (2024)
Universidad Tecnológica de Pereira recognizes the pivotal role of integrating new technologies into its academic procedures, thereby determining its relevance in the societal dynamics that directly influence educational advancement (Dodigovic, 2009; Cotos, 2018; Xiaohong & Yanzheng, 2021). This phenomenon is particularly evident in the domain of Artificial Intelligence (AI), which has brought about significant disruptions in the realm of language education. This chapter presents the outcomes of a research project documenting the integration of AI-powered technologies serving as companions in the academic writing processes of English students enrolled in the B.Ed. in Bilingualism program within the School of Fine Arts and Humanities.